Surface structures, photovoltages, and stability of n-Si(111) electrodes surface modified with metal nanodots and various organic groups - Takabayashi, Susumu (Langmuir : the ACS journal of surfaces and colloids, 2005)
The surface structures, photovoltages, and stability of n-Si(111) electrodes surface-modified with Pt nanodots and organic groups were studied in an I-/I3- redox electrolyte, using alkyls of varied chain length and those having a double bond and ester at the terminal as the organic groups. The n-Si was first modified with the organic groups, and then Pt was electrodeposited on it. Linear sweep voltammetry revealed that, for the modification with alkyls, the overvoltage for the Pt deposition became significantly larger with increasing alkyl chain length, though this does not necessarily hold for the modification with alkyls having a double bond and ester. Scanning electron microscopic inspection showed that the Pt particle density decreased and the particle size increased, with increasing alkyl chain length. The photovoltaic characteristics and stability for the n-Si electrodes modified with the organic groups were much improved by the Pt nanodot coating, though they became somewhat inferior with increasing alkyl chain length. On the basis of these results, it is concluded that surface alkylation at high coverage together with coating with small Pt nanodots gives efficient and stable n-Si electrodes